Unlocking learning: international perspectives on education in prison - McDevitt, Justin; Gellman, Mneesha (Brandeis series in law and society, 2024)
"How can people involved in carceral interventions learn from work in carceral settings outside the United States? This volume addresses this question by gathering international perspectives to the field of education in prison that could inform carceral interventions elsewhere, including in the United States"--